Pantun in the Text of Nyanyian Lagu Melayu Asli (NLMA) - Ritawati, Tengku (Harmonia: Journal of Arts Research and Education, 2018)
The purpose of this study is to understand the role of pantun in the text of Nyanyian Lagu Melayu Asli (NLMA). By using critical descriptive method accompanied by implementation of content analysis theory, the author conducted literature studies (literature studies), namely activities relating to compilation and critical analysis of literature data, such as books, magazines, documents, historical stories and etc. The results of the study found that Pantun is an old Malay poetry work that is not only full of meaning but also solid with its beauty value. Values of beauty can perceived if we are sensitive and susceptible with structure and language style a pack of Pantun. The other result of this study found the functionality of the origin creation of Pantun associated with; (1) commoners who created pantun through their own living experiences, (2) wise people who issued wise words from their contemplation and (3) wise verses from the holy book, namely the Qur'an. The most important research results above all of them are: 1). Pantun as a literary art, which has fulfilled the provisions as one of the highest art works of the Malay heritage. 2). Pantun as a culture of the Malay community confirms that the culture of reciprocating pantun is the culture of the Malay people. 3). Therefore, as the ‘soul’ of NLMA, meaning and aesthetic of a Pantun should be understood and expressed by all NLMA singers.